Implementation of the Regional Hospital Management Information System to Improve the Quality of Operational Services - Adila Khairani Br Tambunan; Muhammad Irwan Padli Nasution; Nurbaiti (LifeSciFi, 2025)
The increasing demand for fast, accurate, and efficient healthcare services has encouraged hospitals to integrate technology into their operations. This study aims to analyze the impact of implementing the Hospital Management Information System on the quality of operational services in the registration department of Aek Kanopan Regional General Hospital. A descriptive quantitative approach with a one-group pretest–posttest design was used to measure changes in employees’ perceptions before and after system implementation. Data were collected from 60 employees selected from a total of 150 using Slovin’s formula with a 10% margin of error, and analyzed using the Wilcoxon Signed Rank Test. The results showed an increase in the mean score of the Hospital Management Information System from 19.9 to 20.6 and in service quality from 20.3 to 20.9, with significance values of 0.007 and 0.029 (p < 0.05), indicating significant improvement. The system enhanced work efficiency, service speed, data accuracy, and inter-unit coordination, although issues such as limited training and network instability remain challenges. Strengthening infrastructure, providing continuous training, and regular evaluations are recommended to optimize the system’s effectiveness and improve hospital service quality.